GEDUNG DEPARTEMEN ARSITEKTUR UNIVERSITAS PALANGKA RAYA : DENGAN PENDEKATAN DEKONSTRUKSI - cherino eduard peyoh, chaziel; Amiany; Yunitha (Jurusan Arsitektur UPR, 2025)
Architecture is a major or field of science that is popular and continues to develop throughout its time. In its development, experienced architecture is needed to serve the needs of the community in construction and design. This is supported by the existence of educational facilities in the form of university architecture departments which have adequate accreditation to produce graduates who are able to compete and are competent in the world of architecture. This can also be supported by making designs with a deconstruction mindset that has a binary understanding or in the sense of the word rebelling against architectural rules, with designs that are able to provide spaces that can develop students' potential and can support in terms of comfort without having to reduce their essence as university/classroom buildings. The method that will be used is design and observation to support data and information both in terms of the architecture department and the deconstruction approach as one of the supports. Later, the architecture department building at Palangka Raya University will support students to be able to produce students who have creativity supported by comfortable buildings and open spaces supported by a deconstruction mindset.